La estructura urbana y las diferencias espaciales en el tiempo de traslado del viaje al trabajo en Ciudad Juárez, Chihuahua - Fuentes Flores, César M. (El Colegio de México A.C., 2008)
The objective of this paper is to address the extent to which the land use (job housing balance, population density, land value), socio-economic characteristics (percentage of low income households and high income households) and housing tenure (percentage of owner-occupied housing and percentage of renter-occupied housing) explains intra urban differences of the commuting time in auto and transit in Ciudad Juarez, Chihuahua. The primary source of data are the Origin-Destination Survey (IMIP) 1997, Housing and Population Census (INEGI), 2000 and Economic Census (INEGI), 1999 all of them at census tract level. Four models were estimated using the ordinary least squares (OLS) statistical method. The findings showed that job housing balance, land value, percentage of renter-occupied housing are statistically significant to explain lower commute time using transit. In contrast, population density and the percentage of owner-occupied housing are statistically significant to explain higher commute time using transit. The percentage of low income households is statistically significant to explain higher commute time using auto.